STUDI KOMPARASI PERKAWINAN BEDA AGAMA DALAM HUKUM NASIONAL DAN FIKIH - Nur Paikah (IAIN BONE, 2019)
AbstractThis study uses a comparative study that seeks to find similarities and differences or compare the similarity of views of interfaith marriages according to national marriage law with fiqh. The basic marriage law in Indonesia is regulated in the Law of the Republic of Indonesia number 1 of 1974. While fiqh in question is the fiqh of four Mazhab in Islam.Interfaith marriage in Law number 1 of 1974 has not been clearly regulated. However, Clause 2 paragraph 1 states that marriage is legal if it is carried out according to the laws of each religious law and its beliefs. It is explicitly understood that if interfaith marriages are not in accordance with religious law, then the marriage cannot be held. This is in line with the marriage of interfaith in fiqh which is basically prohibited.Keywords: Marriage Different Religion; National Law; Jurisprudence.